Differences in Health Care Utilization, Process of Diabetes Care, Care Satisfaction, and Health Status in Patients With Diabetes in Medicare Advantage Versus Traditional Medicare. Issue 11 (November 2020) - Park, Sungchul; Larson, Eric B.; Fishman, Paul; White, Lindsay; Coe, Norma B.
Abstract : Objective: The objective of this study was to determine differences in health care utilization, process of diabetes care, care satisfaction, and health status for Medicare Advantage (MA) and traditional Medicare (TM) beneficiaries with and without diabetes. Methods: Using the 2010–2016 Medicare Current Beneficiary Survey, we identified MA and TM beneficiaries with and without diabetes. To address the endogenous plan choice between MA and TM, we used an instrumental variable approach. Using marginal effects, we estimated differences in the outcomes between MA and TM beneficiaries with and without diabetes. Results: Our instrumental variable analysis showed that compared with TM beneficiaries with diabetes, MA beneficiaries with diabetes had less annual health care utilization, including −22.4 medical provider visits [95% confidence interval (CI): −23.6 to −21.1] and −3.4 outpatient hospital visits (95% CI: −3.8 to −3.0). A significant difference between MA and TM beneficiaries without diabetes was only observed in medical provider visits and the difference was greater among beneficiaries with diabetes than beneficiaries without diabetes (−12.5 medical provider visits; 95% CI: −15.9 to −9.2). While we did not detect significant differences in 5 measures of the process of diabetes care between MA and TM beneficiaries with diabetes, there were inconsistent results in the other 3 measures. There were no or marginal differences in care satisfaction and health status between MA and TM beneficiaries with and without diabetes. Conclusions: MA enrollment was associated with lower health care utilization without compromising care satisfaction and health status, particularly for beneficiaries with diabetes. MA may have a more efficient care delivery system for beneficiaries with diabetes. Abstract : Supplemental Digital Content is available in the text.